Safety and Efficacy of a Novel Anterior Decompression Technique for Ossification of Posterior Longitudinal Ligament of the Cervical Spine. Issue 8 (15th April 2020) - Lee, Dong-Ho; Riew, K. Daniel; Choi, Sung Hoon; Im, Soo Bin; Nam, Woo Dong; Yoon, Young Sik; Hong, Chul Gie
Abstract : Introduction: Anterior cervical corpectomy and fusion (ACCF) for cervical ossification of the posterior longitudinal ligament (OPLL) is associated with a high incidence of surgery-related complications. A novel anterior decompression technique (vertebral body sliding osteotomy [VBSO]) has been developed to prevent such complications. This study attests the efficacy and safety of VBSO versus those of standard ACCF. Methods: Patients requiring surgery for cervical OPLL underwent VBSO (24 patients) or ACCF (38 patients). Operating time, estimated blood loss, neurologic outcomes, complications, and various radiographic parameters were investigated. Results: The VBSO group showed a shorter mean operating time and less estimated blood loss versus the ACCF group. Sixteen patients in the ACCF group experienced various complications, namely neurologic deficit (two patients), cerebrospinal fluid leakage (four patients), graft migration (three patients), and pseudarthrosis (seven patients). In the VBSO group, only pseudarthrosis was reported (two patients). Conclusions: VBSO provides similar neurologic outcomes with a shorter operating time and less bleeding compared with ACCF. Surgeons do not need to directly manipulate the OPLL mass or dissect the interspace between the OPLL and dura mater. Therefore, this technique may decrease the incidence of surgery-related complications. Study Design: Retrospective comparative study.